Disruption of human stratum corneum lipid structure by sodium dodecyl sulphate. (3rd November 2017) - Yanase, K.; Hatta, I.
Abstract: Objective: Surfactants are major ingredients of body soaps and cleansers, and such harsh ones have been demonstrated to damage the skin. Stratum corneum (SC), the outermost barrier of the skin layer, is rich in intercellular lipids. This lipid structure can be disrupted by surfactants, impairing the barrier function of the skin. Thus, we investigated the surfactant‐induced disruption of the intercellular lipid structure of human SC at the molecular level using synchrotron X‐ray diffraction. Methods: SC samples from the breast of female Caucasians were treated with sodium dodecyl sulphate (SDS) and analysed by small‐angle and wide‐angle X‐ray diffraction. Results: We found that an aqueous SDS solution affected the long lamellar structure, which became disorganized. The final disordered lipid state was reached through two or more types of structural change. We propose that the disordered lipid state results from incorporation of SDS into the long lamellar structure. In contrast, the lattice constants in the short lamellar and the hydrocarbon‐chain packing structures remained almost unchanged after SDS treatment. Conclusion: We conclude that the disruption of the long lamellar structure plays a key role in the damage to the SC caused by detergents. To our knowledge, this is the first report to clarify the details of the disorganization of the intercellular lipid structure upon surfactant application. The knowledge obtained herein may allow the development of skin restoration methods and cleanser products that do not affect skin barrier functions.